Determinasi Kinerja Keuangan Pemerintah Kabupaten/Kota Di Provinsi Sumatera Selatan - Jhony Irwan Saputra; Sandrayati; Edwin Frymaruwah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine and analyze the factors that influence financial performance in district/city governments in South Sumatra Province. The data used in this study are financial reports of district/city governments in South Sumatra Province. The population of this study is the financial reports of seventeen districts/cities in South Sumatra Province for the 2018-2022 budget year with a purposive sampling technique and 66 observation units. The data analysis model used is multiple regression. The results of the study show that simultaneously Audit Opinion Revenue, Government Size, and Leverage have a significant effect on the financial performance of local governments. Partially, audit opinion has a negative and significant effect on financial performance, government size has a positive and significant effect on financial performance and leverage has no effect on financial performance.